Still Exhausted: The Role of Residual Caregiving Fatigue on Women in Medicine and Science Across the Pipeline - Katherine A Meese; Laurence M Boitet; Katherine L Sweeney; Lauren Nassetta; Michael Mugavero; Bertha Hidalgo; Rebecca Reamey; David A Rogers (JMIR Publications, 2023)
Understanding the impact of caregiving responsibilities on women in medicine is crucial for ensuring a healthy and intact workforce, as caregiving responsibilities have the potential to affect the careers of women in health care along the entire pipeline, from students and trainees to physicians, physician-scientists, and biomedical researchers.